Libraries as Cultural Agents in Preserving Islamic Values: The Case of Pacu Jalur - Roza, Yanti Mulia; Wazeva, Zilvi; Fadhli, Muhammad (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This article analyzes how a regional library in Indonesia functions as a cultural agent in preserving Islamic values embedded in the Pacu Jalur tradition. Grounded in a cultural literacy framework, this study employs a qualitative case study approach, with primary data collected through in-depth interviews with 12 key informants (librarians, community leaders, and users), participatory observation, and document analysis at the Kuantan Singingi Library and Archives Office. The findings reveal that the library implements three-pronged strategy: curating specialized collections, organizing community-based literacy activities, and utilizing digital media for wider dissemination. The study’s core novelty lies in its effort to bridge library science and local cultural studies, offering an alternative model for how institutional actors can systematically safeguard living traditions as expressions of Islamic civilization. The analysis also affirms the role of libraries in sustaining values such as ukhuwwah (brotherhood), discipline, and spirituality, while noting challenges related to limited resources and digital infrastructure. The article concludes by proposing practical strategies—including digitization, cross-sector partnerships, and librarian capacity building—to strengthen libraries as custodians of local Islamic heritage. Artikel ini menganalisis peran perpustakaan daerah sebagai agen budaya dalam melestarikan nilai-nilai Islam dalam tradisi Pacu Jalur. Berlandaskan kerangka literasi budaya, studi kualitatif kasus ini mengumpulkan data primer melalui wawancara mendalam dengan 12 informan kunci (pustakawan, tokoh masyarakat, dan pengguna), observasi partisipatif, dan analisis dokumen pada Dinas Perpustakaan dan Kearsipan Kabupaten Kuantan Singingi. Hasil penelitian mengungkap tiga strategi utama: penyediaan koleksi khusus, penyelenggaraan kegiatan literasi berbasis komunitas, dan pemanfaatan media digital untuk diseminasi. Kebaruan inti penelitian ini terletak pada upaya menjembatani ilmu perpustakaan dan studi budaya lokal secara empiris, menawarkan model alternatif tentang bagaimana aktor kelembagaan dapat secara sistematis menjaga tradisi hidup sebagai ekspresi peradaban Islam. Studi ini juga menegaskan peran perpustakaan dalam menjaga nilai-nilai seperti ukhuwwah, disiplin, dan spiritualitas, sekaligus menyoroti keterbatasan sumber daya dan infrastruktur digital. Artikel ditutup dengan menawarkan sejumlah strategi praktis—termasuk digitalisasi, kemitraan lintas sektor, dan peningkatan kapasitas pustakawan—untuk memperkuat perpustakaan sebagai penjaga warisan Islam lokal.